Modifiable factors for irritable bowel syndrome: evidence from Mendelian randomisation approach - Jinling Tang; Zhirong Yang; Shanshan Wu; Feng Sha; Tengfei Lin; Di Liu; Meiling Cao; Yiwen Jiang; Weijie Cao; Fuxiao Li (eGastroenterology)
Background The potential modifiable factors influencing irritable bowel syndrome (IBS) have not been thoroughly documented. We aimed to systematically investigate the modifiable factors associated with IBS, while accounting for the impact of unobserved confounders and coexisting disorders.Methods Genetic correlation and Mendelian randomisation (MR) analyses were integrated to identify potential modifiable factors and coexisting disorders linked to IBS. Subsequently, multiresponse MR (MR2) was employed to further examine these associations. Summary-level genome-wide association data were used. Modifiable factors and coexisting disorders (ie, gastrointestinal and psychiatric disorders) were identified based on evidence from cohort studies and meta-analysis. In all analyses, IBS was the primary outcome, while in the MR2 analysis, coexisting disorders were also treated as outcomes alongside IBS.Results Most identified modifiable factors and coexisting disorders exhibited genetic correlations with IBS. MR analyses revealed strong causation between IBS and multisite chronic pain (OR=2.20, 95% CI 1.82 to 2.66), gastro-oesophageal reflux disease (OR=1.31, 95% CI 1.23 to 1.39), well-being spectrum (OR=0.17, 95% CI 0.13 to 0.21), life satisfaction (OR=0.31, 95% CI 0.25 to 0.38), positive affect (OR=0.30, 95% CI 0.24 to 0.37), neuroticism score (OR=1.20, 95% CI 1.16 to 1.25) and depression (OR=1.50, 95% CI 1.37 to 1.66). Additionally, smoking, alcohol frequency, college or university degree, intelligence, childhood maltreatment, frailty index, diverticular disease of the intestine and schizophrenia were suggestively associated with IBS. Robust associations were found between multisite chronic pain and both IBS and coexisting disorders.Conclusions Our study identified a comprehensive array of potential modifiable factors and coexisting disorders associated with IBS, supported by genetic evidence, including genetic correlation and multiple MR analyses. The presence of multisite chronic pain may offer a promising avenue for the concurrent prevention of IBS and its coexisting disorders.